Multinational Enterprise, Political Risk and Organisational Change From Total War to Cold War (Taylor & Francis, 2019)
Multinationals, Organizational Change, Total War, War and Industry, Business History, Accounting History, Cold War, Organizational Innovation
English
Keywords: Business & management; Economic history; History of specific companies / corporate history; Organizational theory & behaviour; Multinationals, Organizational Change, Total War, War and Industry, Business History, Accounting History, Cold War, Organizational Innovation